Empowering women farmer groups through post-harvest innovation: Upgrading and marketing California papaya products in Sleman - Retty Ikawati; Arsyad Cahya Subrata; Titisari Juwitaningtyas; Fityatul Nurbaiti; Haidar Usman Hakim; Amiresti Hakimatul Mahira; Ainin Nuzha Izzatin Fauzia; Azfa Rahmawan (Community Empowerment, 2026)
The "Rejoarum" Women Farmer Group (KWT) in Pandowoharjo, Sleman, has successfully diversified their local California papaya harvest into three distinct value-added products: Payachips (papaya chips), Papaku (papaya seed coffee substitute), and Noripaya (papaya leaf savory seasoning). Despite these innovations, the group faces significant bottlenecks in product commercialization and market penetration. This community service initiative aims to resolve these downstream challenges by delivering targeted training in advanced food packaging and strategic marketing. The program was executed through a structured framework involving program socialization, hands-on packaging workshops, and strategic business formulation using the Business Model Canvas (BMC). The intervention yielded substantial capacity growth, with participants' understanding soaring to a post-test range of 37%–100%, a marked improvement from the baseline pre-test range of 10%–90%. Tailored marketing frameworks were also established for each product variant based on distinct consumer segments. Ultimately, this training has equipped KWT Rejoarum with the vital entrepreneurial skills and insights necessary to optimize post-harvest management and sustain resilient, independent production cycles.